We could use any of these numbers to start off.
We can either choose to solve for x or y it doesn't matter. I will start by solving for y in `6x + 9y =-3`
The first step is to move 6x to the other side by subtracting it because we are trying to get y alone.
`9y = -3 - 6x`
Now divide by 9 because it is standing in the way of y:
`y = -3/9 - (6x)/9`
We can simplify these:
`y = -1/3 - (2x)/3 `
Now plug in these numbers as Y on the other problem:
`-4x - 6(-1/3 - (2x)/3) = 11 `
distribute the -6
`-4x + 2 + 4x = 11 `
combine like terms:
`-4x + 4x + 2 = 11 `
2 `!=` 11
therefore there are no numbers that could satisfy this equation.